Exploring Seasonality Indices for Low-Flow Analysis on Tibagi Watershed (Brazil) - Alexandre Sokoloski de Azevedo Delduque de Macedo; Michael Männich (Hydrology)
This study investigated the seasonality of low-flow discharges in the Tibagi watershed, Paraná, Brazil, through the analysis of three indices: Seasonality Ratio (<semantics>SR</semantics>), Seasonality Index (<semantics>SI</semantics>), and Seasonality Histogram (<semantics>SH</semantics>). The indices were computed and compared using previously calculated low-flow discharge data (<semantics>Q95</semantics>) and physiographic information on sub-watersheds. A ‘Seasonality Calendar’ was developed, illustrating the period and intensity of low-flow discharge occurrences in the watershed. The results indicate that, despite the watershed not presenting a strong seasonality, there is a tendency for low-flow discharges to concentrate in certain months, notably in August, September, and October. Spatial analysis reveals varied patterns with a certain trend of increased seasonality intensity (parameter r) towards downstream (north) and as the watershed area increases. These indices emerge as valuable tools for water resource management, aiding decision-making for allocation and hydrological regionalization, such as optimizing granting water resource distribution during dry seasons based on the identified low-flow patterns and establishing different reference low-flow values throughout the year.